2014
DOI: 10.1016/j.jtcvs.2013.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of electrocerebral inactivity with deep hypothermia

Abstract: Objective Cooling to electrocerebral inactivity (ECI) by electroencephalography (EEG) remains the gold-standard to maximize cerebral and systemic organ protection during deep hypothermic circulatory arrest (DHCA). We sought to determine predictors of ECI to help guide cooling protocols when EEG monitoring is unavailable. Methods Between July 2005 and July 2011, 396 patients underwent thoracic aortic operation with DHCA; EEG monitoring was utilized in 325 (82%) of these cases to guide the cooling strategy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 20 publications
0
38
0
2
Order By: Relevance
“…Total arch replacement is similarly performed for aneurysm or extensive destruction of the transverse arch. For hemi-or total arch repair, the open distal anastomosis is completed under a period of moderate hypothermic circulatory arrest (HCA) (28) with intraoperative electroencephalographic (EEG) monitoring, when available (29,30). In the unmonitored cases, patients are cooled until the nasopharyngeal temperature is <24 ℃ as prior work from our group has demonstrated that EEG findings suggestive of cerebral ischemia occur more frequently following onset of HCA at warmer temperatures (28).…”
Section: Patient Selection and Operative Techniquementioning
confidence: 99%
“…Total arch replacement is similarly performed for aneurysm or extensive destruction of the transverse arch. For hemi-or total arch repair, the open distal anastomosis is completed under a period of moderate hypothermic circulatory arrest (HCA) (28) with intraoperative electroencephalographic (EEG) monitoring, when available (29,30). In the unmonitored cases, patients are cooled until the nasopharyngeal temperature is <24 ℃ as prior work from our group has demonstrated that EEG findings suggestive of cerebral ischemia occur more frequently following onset of HCA at warmer temperatures (28).…”
Section: Patient Selection and Operative Techniquementioning
confidence: 99%
“…bei der ein isoelektrisches EEG auftritt), unterschiedlich[55]. Beispielsweise schwanken die Angaben über die nasopharyngeale Temperatur, bei der ein isoelektrisches EEG einsetzt, zwischen 26 und 10°C[56,57]. Insgesamt kann das prozessierte EEG-Monitoring bei tiefer Hypothermie kaum zur Beurteilung einer adäquaten Narkosetiefe genutzt werden.…”
unclassified
“…A total of 358 cases (81.4%) were monitored, as previously described. 14,15 In brief, the patients were cooled until electrocerebral inactivity was reached, after which, DHCA was begun. Electrocerebral inactivity ensures maximal metabolic suppression of the brain and, therefore, maximal neurocerebral protection.…”
Section: Methodsmentioning
confidence: 99%